Analisis Jaminan Dalam Akad-Akad Bagi Hasil (Akad Mudharabah dan Akad Musyarakah) Di Perbankan Syariah - Islami, Aufa (Jurnal Hukum Ekonomi Syariah, 2021)
This research is entitled Analysis of Guarantees in Profit Sharing Contracts (Mudharabah and Musyarakah contracts) in Islamic banking. This research was conducted with the aim of analyzing the guarantees contained in profit sharing contracts including the Mudharabah contract and the Musyarakah contract in Islamic Banking. This article research uses a normative approach. The normative approach is used for research from the perspective of fiqh muamalat regarding the position of the guarantee in the profit sharing contract. From this research it can be concluded that basically there is no guarantee for profit sharing contracts, such as mudarabah and musyarakah, except as a guarantee of the possibility of moral hazard being carried out by the contract partners. In practice, Islamic financial institutions, especially Islamic banking, always withdraw material guarantees for the profit sharing contracts they cover with their partners (customers). However, it must be remembered that the withdrawal of the material guarantee must be limited to cases where there is a loss due to unlawful acts, negligence or default by the customer. In the event that the loss occurs beyond the customer's fault, negligence or breach of contract, the guarantee may not be executed.